2023
DOI: 10.1186/s12913-023-09756-2
|View full text |Cite
|
Sign up to set email alerts
|

Support for relatives in the intensive care unit: lessons from a cross-sectional multicentre cohort study during the COVID-19 pandemic

Abstract: Background Support for relatives is highly important in the intensive care unit (ICU). During the first COVID-19 wave  support for relatives had to be changed considerably. The alternative support could have decreased the quality and sense of support. We aimed to evaluate how support for relatives in Dutch ICUs was organised during the first COVID-19 wave and how this was experienced by these relatives in comparison to relatives from pre-COVID-19 and the second wave. Additionally, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…Family support teams reprieved nurses of the time needed for effective care partner support. These findings are consistent with other recommendations that FSTs or nurse liaisons can mitigate nurse distress when visitation is limited 21 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Family support teams reprieved nurses of the time needed for effective care partner support. These findings are consistent with other recommendations that FSTs or nurse liaisons can mitigate nurse distress when visitation is limited 21 …”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with other recommendations that FSTs or nurse liaisons can mitigate nurse distress when visitation is limited. 21 Similarly, many studies demonstrate that the teamwork and solidarity experienced by nurses during periods of restricted visitation were emotionally protective. 8,22 Family support teams and nurse liaisons, often composed of redeployed procedural nurses, leverage the cohesion and support that are known to reduce burnout and stress in nurses.…”
Section: Technology To Aid Communicationmentioning
confidence: 99%
“…Kang et al's [28] meta-analysis identi ed family participation, information provision, lighting and noise blocking as effective in preventing delirium, which can all be classi ed as PCC interventions. Recent studies [29,30] have reported that virtual visiting or video calling to replace visiting restrictions during the COVID-19 pandemic was effective in preventing delirium and reducing psychological distress in ICU patients. Despite these encouraging outcomes, a meta-analysis found insu cient evidence of signi cant effects of PCC interventions on post-discharge mental health and ICU delirium [25].…”
Section: Discussionmentioning
confidence: 99%
“…It combined a retrospective questionnaire study with a subsequent qualitative in-depth semi-structured interview study. This study is part of a larger study among relatives of ICU patients, both discharged and deceased, which also addressed other topics such as important elements of support [ 20 ] and treatment decision-making [ 21 ]. As the current study is about aftercare for bereaved relatives, only data from relatives of ICU patients who died in the ICU were included.…”
Section: Methodsmentioning
confidence: 99%
“…During the first COVID-19 wave, three of the six ICUs used newly developed family support teams, which consisted of non-ICU healthcare professionals, who supported relatives via telecommunication. In the other three ICUs, healthcare professionals from the ICU continued to provide the support themselves, but also via telecommunication [ 20 ].…”
Section: Methodsmentioning
confidence: 99%